Here's the question you clicked on:
JenniferSmart1
Why is this true? \[\vec E \cdot d \vec l=E \hat i \cdot (dx \hat i +dy \hat j +dz \hat k)=E dx\] I understand the first part \[\vec E \cdot d \vec l=E \hat i \cdot (dx \hat i +dy \hat j +dz \hat k)\] but how does that equal Edx?
@zepdrix @hartnn
i and j are perpendicular i and k are perpendicular
i.i = i^2 = 1 i.j =0 i.k=0
I'm sorry...but how did you determine that they were perpendicular?
i , j and k are standard unit vectors. i is along x direction j is along y direction k is along z direction and axes are perpendicular to each other, right ?
|dw:1361080799293:dw| any more doubts ?
ahhhh.....nope...no more doubts =D